Analgesic, Anti-Inflammatory and Anti-Biofilm-Forming Activity of Potato (Solanum tuberosum L.) Peel Extract - Wahyudi, Ivan Arie; Ramadhan, Fahri Reza; Wijaya, Rama Insan Kusuma; Ardhani, Retno; Utami, Trianna Wahyu (Indonesian Society for Cancer Chemoprevention, 2020)
The utilization of natural resources, one of which is plants, has been researched as an alternative to synthetic drugs because of their natural content. Potato (Solanum tuberosum L.) peels, the parts of potatoes that are often cut off and discarded, have been reported to have some phenolic compounds and flavonoids in their composition. The extract of potato peels was investigated for its analgesic, anti-inflammatory, and anti-biofilm-forming properties. A hot plate test was conducted to assess the analgesic activity in treatment doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg with paracetamol as the reference drug and distilled water as the negative control, while carrageenan-induced paw edema was used to assess anti-inflammatory activity in treatment doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg with diclofenac as the reference drug and distilled water as the negative control. Anti-biofilm-forming activity was tested by using the crystal violet assay. The results showed that, compared with the negative control, treatment doses of 100 mg/kg and 200 mg/kg significantly (p < 0.05) reduced pain stimuli, whereas a treatment dose of 100 mg/kg, 200 mg/kg, and 400 mg/kg significantly (p < 0.05) reduced the edema volume increment. However, compared with the positive control, paracetamol and diclofenac were associated with the least pain stimulus and the least edema volume increment, respectively. Potato peel extract against S. mutans biofilm formation demonstrated effectiveness (p < 0.05). Based on these data, it can be concluded that potato peel extract has analgesic, anti-inflammatory, and anti-biofilm-forming activities, as demonstrated in this study.